ACID GAS ABSORPTION STUDIES IN PACKED COLUMN (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Carbon dioxide is a major greenhouse gas that results in climatic changes. Reducing CO2 emission for addressing the climatic change concerns is becoming increasingly important as the CO2 concentration in the atmosphere has increased rapidly since the industrial revolution. Many mitigation methods, including CO2 sequestration and novel CO2 utilization, are currently under investigation. Most of these processes require CO2 in a concentrated form. However the CO2 from large sources such as fossil fueled power plants is mixed with nitrogen, water vapor, oxygen and other impurities. The current commercial operations for capturing CO2 from flue gas use a chemical absorption method with Monoethanol Amine (MEA) as the sorbent. The method is expensive and energy intensive. The cost of capturing a ton of CO2 including removing impurities and compressing CO2 to supercritical pressure using existing MEA technology would be very high, and the power output would be significantly reduced by the energy consumption in capturing and compressing CO2. In this work alternative solvent ammonia, is used which can overcome the disadvantages of current technology using amines such as MEA and DEA.